Occupational risks in agricultural work and the negotiation for the health of rural workers - Leticia Silveira Cardoso; Clarice Alves Bonow; Daiani Modernel Xavier; Marta Regina Cezar-Vaz (Universidade Federal de Santa Maria, 2021)
Objective: to understand the relationship between occupational risks in agricultural work and the negotiation for the health of rural workers. Method: mixed nested concurrent study, combined with equal integration (QUAN + QUAL). It was conducted with 351 farmers, between 2014/2015, using a form and semi-structured interview. For the analysis, descriptive and inferential statistics and the descending hierarchical classification, and the word cloud were used. Results: in the QUAN phase, the average age of 50.58 years old was obtained and a predominance of symptoms of illness in the muscular, endocrine, and urinary systems. In the QUAL phase, it became evident that the negotiation of agricultural products increases the exposure of workers to physical, chemical, and ergonomic risks. Profit represents the goal and allows for the cost of equipment, health care, and drug therapy, through illness. Conclusion: occupational risks are present in agricultural work. Negotiation is reduced to the consumption of health services and products in the presence of illness.